Implementasi Prosedur Clean Install Sistem Operasi Windows 10 pada Perangkat Keras dengan Variasi Spesifikasi : Pendekatan Sistematis Berbasis Pengujian Empiris - Silveria Anita Sari Dakhi; Pernando Alvonso Situmorang; Wira Amin; Fauzia Pulungan; Sahat Parulian Sitorus (Universitas Labuhanbatu, 2026)
This study empirically examines the clean install procedure of the Windows 10 operating system on hardware with varying configurations. The research was motivated by the high rate of installation failures due to the absence of standardized procedural guidelines in academic and office environments. The research objective is to design and validate a systematic installation procedure, identify technical factors affecting installation success and duration, and produce a widely adoptable guide. A comparative experimental method was employed by testing the procedure on ten computer units divided into two groups based on storage media type: Hard Disk Drive (HDD) and Solid State Drive (SSD). Results show that SSD-based devices completed installation an average of 45.1% faster than HDDs, with average times of 17.8 minutes versus 32.4 minutes. The installation success rate reached 100% in the SSD group and 80% in the HDD group, where failures were caused by bad sectors undetected prior to installation. The research concludes that thorough hardware health inspection before installation and the use of official Microsoft installation media are the two most critical factors in ensuring a successful Windows 10 clean install.